Frailty Predicts Mortality after Heart Transplantation. (July 2018) - Jha, Sunita; Newton, Phillip; Montgomery, Elyn; Hayward, Christopher; Jabbour, Andrew; Muthiah, Kavitha; Kotlyar, Eugene; Connellan, Mark; Dhital, Kumud; Granger, Emily; Jansz, Paul; Spratt, Phillip; et al.
Abstract : Background: We have previously reported that combining cognitive assessment with the Fried frailty phenotype (FFP) enhances mortality prediction in advanced heart failure (AHF) patients referred for VAD or heart transplant (HTx) assessment (J Heart Lung Transplant 2016;35:1092-100). In this study, we examined the impact of frailty on post-HTx outcomes. Methods: Ninety-six patients (53 men; 43 women) who underwent assessment of cognition and frailty within 12 months of HTx between 2013 and 2017 were included in the study. Frailty was defined as > 3 physical domains of the Fried Frailty Phenotype (FFP) or > 2 physical domains of the FFP plus cognitive impairment defined as a score of < 26/30 on the Montreal Cognitive Assessment (MoCA). Depression screening was also performed using the Depression in Medical Illness (DMI-10) score. Results: Average time between frailty assessment and HTx was 4.5 + 3.1 months. Thirty were classified as frail (F), and 66 were not frail (NF). There was no significant difference in age (48.2±14 F vs 50.6±15, p=0.46), or BMI (24.9±5.5 vs 24.8±4.2, p=0.92) between groups, but a higher proportion of women than men were frail (42% vs 23%, p < 0.05). Pre-transplant mechanical support was utilised in a similar proportion of F (n=8/30) and NF (n=12/66) patients (p = 0.34). As expected, mean MoCA scores were lower in the F group (24 ± 4 vs 26 ± 3, p=0.0037). Depression as defined by a DMI score > 9 was also more common in the F group (53% vs 26%, p = 0.01). Frailty was an independent predictor of all-cause mortality after HTx with 1 yr survival 74 + 9% in the F group, compared to 98 + 2% in the NF group (p = 0.0003). There were trends towards longer median intubation times, ICU and hospital length of stay in the F group but differences were not significant. Conclusions: Similar to our previous finding that frailty was an independent predictor of mortality in AHF patients referred for HTx assessment, frailty was also an independent predictor of mortality after HTx. These findings may help us better identify patients who will benefit most from transplant. NHMRC Program Grant 1074386.